2011
DOI: 10.1007/s10571-011-9746-6
|View full text |Cite
|
Sign up to set email alerts
|

Activation of ERK1/2 and PI3K/Akt by IGF-1 on GAP-43 Expression in DRG Neurons with Excitotoxicity Induced by Glutamate In Vitro

Abstract: Insulin-like growth factor-1 (IGF-1) is a neurotrophic factor and plays an important role in promoting axonal growth from dorsal root ganglion (DRG) neurons. Whether IGF-1 influences growth-associated protein 43 (GAP-43) expression and activates the extracellular signal-regulated protein kinase (ERK1/2) and the phosphatidylinositol 3-kinase (PI3K)/Akt signaling pathways in DRG neurons with excitotoxicity induced by glutamate (Glu) remains unknown. In this study, embryonic 15-day-old rat DRG explants were cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
23
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 46 publications
4
23
0
Order By: Relevance
“…Moreover, Liu and colleagues reported that IGF-1 might have a neuroprotective effect by regulating GAP-43 expression. The action was completed through both ERK1/2 and PI3K/Akt activation [25]. Our findings are in conformity with Liu's report and suggest that CST axonal regeneration is mediated by soluble factors secreted from BMSCs in the study.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, Liu and colleagues reported that IGF-1 might have a neuroprotective effect by regulating GAP-43 expression. The action was completed through both ERK1/2 and PI3K/Akt activation [25]. Our findings are in conformity with Liu's report and suggest that CST axonal regeneration is mediated by soluble factors secreted from BMSCs in the study.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, IGF-1 activates Erk1/2-MAPK signaling [30] and Erk1/2 is activated by PI3K/ Akt [31]. Suppression of Erk1/2 phosphorylation upregulates Smad2/3 phosphorylation and enhances cellular differentiation [32].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the restoration of visual function is achieved, albeit with a delay, even after LIF knockdown. The GAP-43 gene expression is regulated not only by Jak/STAT3 signaling, but also by the extracellular signal-regulated kinase 1/2 and phosphatidylinositol 3-kinase (PI3K)/Akt pathway [48]. The latter is indeed activated during fish optic nerve regeneration [49].…”
Section: Discussionmentioning
confidence: 99%